Using Reading Questioning Answering (RQA) Model to Improve Student Reading Skill During Online Learning - Feby Ardini; Muhamad Sofian Hadi; Aswir Aswir (Jurnal Studi Guru dan Pembelajaran, 2022)
This research is motivated by the lack of reading interest in students at MTS Khazanah Kebajikan which affects online learning activeness in increasing reading interest, student understanding and students' critical thinking skills. As we already know, online learning makes learning less effective because students can easily answer all questions from the internet without reading in detail, but there are also students who are hampered in terms of facilities, technology and networks. This study uses a descriptive qualitative method based on information data collection, interviews and observations about the problems or difficulties of students during online learning and especially in increasing students' reading interest. The main target of this research is students at MTS Khazanah Kebajikan, where students lack reading interest during online learning. With the RQA model it can be seen how high the level of students 'reading interest is during online learning and can optimize students' understanding at school. Keyword: Education, Online Learning, Reading Interest, RQA